The Effect of Thermal Conditions on Airflow and Heat Transfer in a Test Object: An Experimental Study - Hilmala Nurmualimah; Nur Rohmat; Alvian Harris Gita Purnama (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This research aims to analyze the influence of thermal conditions; specifically the temperature difference between the test object and the environment; on the characteristics of air flow and heat transfer around it. The object of this study is a test piece subjected to free air flow under various temperature conditions; focusing on the convection heat transfer phenomenon. The main problem addressed is how temperature variations affect the convection heat transfer coefficient; heat transfer rate; and heat flux; as well as changes in air velocity and pressure profiles. Therefore; the objective of this research is to quantitatively compare and assess these thermal and fluid parameters through an experimental study approach and Computational Fluid Dynamics (CFD) simulation. The methodology involves direct measurement of temperature and pressure parameters under low and high-temperature conditions; which are then processed to determine the convection coefficient (); heat transfer rate (); and heat flux (). The main findings indicate that at low-temperature conditions; the heat transfer coefficient () was found to be 53.26 ; the heat transfer rate () was 24.99 W; and the heat flux () was 537.87 ; with a pressure drop of 0.86 Pa. In conclusion; thermal conditions play a crucial role in determining the dynamics of air flow and the efficiency of heat transfer; the greater the temperature difference (); the higher the potential heat transfer rate; establishing a strong correlation between thermal conditions and the convection phenomenon.